Reflectance spectral characterization of acid sulphate soil in South Yunderup, Western Australia - Shi, Xianzhong; Aspandiar, Mehrooz; Oldmeadow, David (Taylor and Francis Ltd, 2014)
Acid sulphate soils (ASS) are widely spread worldwide and are detrimental to theenvironment. South Yunderup is one of the coastal areas of Western Australia heavilyaffected by ASS. Conventional investigation is costly and time-consuming, and thusthere is an urgent need to rapidly characterize and identify this type of soil. This paperaims to characterize these soils using reflectance spectra, which may be one of themost significant steps in effectively identifying them and mapping their extent byremote sensing. The ASS from the study area were divided into several groups andsubtypes according to both pH measurements and mineral composition as identified byX-ray diffraction analysis. Each group and subtype was then characterized by itsspectral reflectance features. We found that the spectral characteristics of ASS aregoverned by the spectral features of its compositional minerals. In particular, somesecondary iron-bearing minerals produced by the formation of ASS, together withsurrounding minerals such as carbonate, play vitally important roles in influencing thespectral characterization of ASS. These iron-bearing minerals, including iron oxides,hydroxides/oxyhydroxides (e.g. haematite, goethite, and ferrihydrite), and iron sulphates(e.g. jarosite and copiapite), have diagnostic spectral features and are thereforedetectable in the reflectance range. Moreover, these secondary iron-bearing mineralscould be indicators suggesting the pH conditions in which they formed. The results ofthis study include the overall mineral distribution of the study area, the spectralcharacterization of different groups and subtypes of ASS, and the linkages betweenspectral features and pH ranges.